Thomas and the Thomists : The Achievement of Thomas Aquinas and his Interpreters - Cessario, Romanus; Cuddy, Cajetan (Mapping the tradition., 2017)
Thomas and the Thomists, a new volume in the Mapping the Tradition series, serves as an introduction to the life of Aquinas, the major contours of his teaching, and the lasting contribution he made to Christian thought. Romanus Cessario and Cajetan Cuddy also outline the history of the Thomist tradition from the medieval era through revival in the nineteenth and twentieth centuries. This volume affords its readers a working guide to understanding the history of Aquinas and his expositors as well as to grasping their significance for us today.